Clinical Short-term outcomes for laser hemorrhoidoplasty for grade II and III haemorroidal disease: experience in Bangladesh - Majumder, Krisna Rani; Rassell, Md; Pervin, Mosammat Mira; Kamal, Md Faysal (Journal of Surgical Sciences, 2021)
Introduction: Hemorrhoidal Diseases are a common medical condition affecting individuals worldwide, with grades II and III being considered mild to moderate stages. Laser hemorrhoidoplasty has emerged as a potential alternative to traditional surgical techniques, offering reduced postoperative pain and faster recovery times. Objective: The primary objective of this study is to evaluate the efficacy and safety of laser hemorrhoidoplasty in grade II and III hemorrhoidal disease within a short-term follow-up period. Methods: This is a retrospective study conducted at Anower Khan Modern Hospital; Dhaka, Care Hospital; Dhaka & Peerless Hospital; Naogaon, Bangladesh spanning from March 2019 to April 2023. Patients diagnosed with grade II and III hemorrhoidal disease who underwent laser hemorrhoidoplasty were included in the analysis. Data on patient demographics, pre-operative symptoms, procedural details, and post-operative follow-up visits were collected and analyzed. Results: In this study, 255 patients underwent laser hemorrhoidoplasty for grade II and III hemorrhoidal disease at Anower Khan Modern Hospital; Dhaka, Care Hospital; Dhaka & Peerless Hospital, Naogaon (March 2019 to April 2023). Overall, laser hemorrhoidoplasty showed promising short-term outcomes for grade II and III hemorrhoidal disease, with effective symptom relief and minimal postoperative discomfort. Conclusion: Laser hemorrhoidoplasty shows promise as a safe and efficient alternative treatment, warranting further investigation with larger cohorts and longer follow-up periods to validate its efficacy and safety. Journal of Surgical Sciences (2021) Vol. 25(2) : 15-21